Potentiometric and Spectrophotometric Determination of the Stability Constants of Luteolin (3′,4′,5,7-Tetrahydroxyflavone) Complexes with Aluminium(III) and Iron(III) - (:unkn) unknown (My University, 2003)
In this study, one determined stability constants of the complexes of luteolin with aluminium (III) and iron(III). Potentiometric methods of Calvin-Bjerrum and Irving-Rossotti, and spectrophotometric assay have been utilised. The evaluated protonation constants of the ligand were: logk 1 = 8.95, logk2 = 8.10, and logk3 = 6.85 at the 25°C. For the aluminium and iron complexes the subsequent logarithms of formation constants were found: for Al 17.50, 15.00, 4.75 and for iron: 19.60, 19.40, 17.82.
Keywords: Aluminium; Formation constant; Iron; Luteolin; Protonation constants